Cholesterol metabolism regulated by CAMKK2-CREB signaling promotes castration-resistant prostate cancer - Chenchu Lin; Thomas L. Pulliam; Jenny J. Han; Jiaqian Xu; Carlos Vera Recio; Sandi R. Wilkenfeld; Yan Shi; Manoj Kushwaha; Sarah Bench; Eduardo Ruiz; Sanjanaa Senthilkumar; Jayasurya Dileep; et al. (Cell Reports)
Summary: Castration-resistant prostate cancer (CRPC) remains an incurable disease in need of improved treatments. CAMKK2 is an emerging therapeutic target whose oncogenic effects in prostate cancer have, to date, been largely attributed to its activation of AMP-activated protein kinase (AMPK). Here, we demonstrate that CAMKK2 promotes prostate cancer growth through an alternative downstream pathway involving CAMKI and CREB. Unbiased transcriptomics identify CREB-mediated transcription as a CAMKK2-regulated process, findings that we validate using diverse molecular, genetic, and pharmacological approaches in vitro and in vivo. CAMKK2 promotes CREB phosphorylation/activation through CAMKIα independently of AMPK, CAMKIV, or other CAMKI isoforms. Functionally, the CREB family members CREB1 and ATF1 exhibit close redundancy, necessitating co-targeting for optimal anti-tumor efficacy. An inhibitor of CREB1/ATF1 blocks CRPC with minimal side effects. Mechanistically, CAMKK2 and CREB increase CRPC growth through augmenting cholesterol metabolism. Together, these findings identify an oncogenic pathway that could be exploited for the treatment of CRPC.